Dietary supplementation of α-linolenic acid induced conversion of n-3 LCPUFAs and reduced prostate cancer growth in a mouse model - Jingjing Li; Zhennan Gu; Yong Pan; Shunhe Wang; Haiqin Chen; Hao Zhang; Wei Chen; Yong Q. Chen (Lipids in Health and Disease, 2017)
Abstract Background α-linolenic acid (ALA) is an n-3 polyunsaturated fatty acid (PUFA) and the substrate for long-chain n-3 PUFAs. The beneficial effects of ALA on chronic diseases are still in dispute, unlike those of eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA). Methods The primary objective of this investigation was to evaluate the efficiency of ALA uptake from a vegetable oil source and its subsequent conversion to n-3 long-chain PUFAs (LCPUFAs) in the tissues of growing mice, and to investigate its protective role in a prostate cancer animal model. We carried out the investigation in prostate-specific Pten-knockout mice with specified low-ALA (L-ALA, 2.5%) and high-ALA (H-ALA, 7.5%) diets. Total fatty acids in blood, liver, epididymal fat pad, prostate were detected and prostate weight were adjusted for body weight (mg/25 g). Results We found that dietary ALA triggered significant increases in ALA, EPA, docosapentaenoic acid (DPA) and DHA levels and a significant decrease in arachidonic acid levels during the mice’s growth stage. A dose-dependent effect was observed for ALA, EPA and DPA, but not DHA. Furthermore, the average prostate weights in the L-ALA and H-ALA groups were lower than those in the control and n-6 groups, and similar to those in the EPA and n-3 groups. Conclusions Our data suggest that dietary supplementation with ALA is an efficient means of improving n-3 LCPUFAs in vivo, and it has a biologically effective role to play in prostate cancer, similar to that of fish oils.